The Effect of Exclusive Breastfeeding Education Through Audio-Visual Media on the Knowledge Level of Third Trimester Pregnant Women - Desi Laela Fitasari; Wulan Margiana (Lembaga Pengembangan Kinerja Dosen, 2025)
Breast milk is the best food for babies 0-6 months. Indonesia's exclusive breastfeeding coverage in 2022 was recorded at only 67.96%, down from 69.7% in 2021. The cause of the lack of exclusive breastfeeding is influenced by several factors, one of which is the mother's knowledge about exclusive breastfeeding. One way to increase exclusive breastfeeding is to carry out health promotion through audio-visual media. This study aims to determine the Effect of Exclusive Breastfeeding Education Through Audio-Visual Media on the Knowledge of Third Trimester Pregnant Women at Wangon II Health Center. This study used pre-experimental research, with one group pretest-posttest design evaluation experiment through pretest-postest. The study sample was 35 pregnant women in the third trimester who were given treatment in the form of exclusive breastfeeding socialization with adio-visual media. The results of the experimental group's Wilcoxon test obtained a p value (0.000) ≤ 0.05, this shows that there are differences in knowledge level about exclusive breastfeeding in pregnant women before and after being given educational interventions using audiovisual media.